2004
DOI: 10.1046/j.1529-8817.2004.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

The FBN1 (R2726W) mutation is not fully penetrant

Abstract: SummaryThe R2726W mutation in the fibrillin 1 (FBN1, Marfan syndrome) gene segregates with isolated skeletal features of Marfan syndrome and/or high stature. Here we report a family in which two out of four individuals, an 18-year-old son and his mother, a 41-year-old woman, had the R2726W mutation of FBN1. Both family members carrying the mutation were of average height. The son had a Marfan-like phenotype, but his mother did not. The FBN1 R2776W mutation, which is associated with skeletal features of Marfan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…It is important to remark that a genetic variant in the FBN1 gene has been previously described in a patient with Marfan syndrome who also suffered epilepsy. However, in this family no other Marfan trait was present [24]. The variant detected in HCN1 gene is a deletion of three amino acids.…”
Section: Discussionmentioning
confidence: 83%
“…It is important to remark that a genetic variant in the FBN1 gene has been previously described in a patient with Marfan syndrome who also suffered epilepsy. However, in this family no other Marfan trait was present [24]. The variant detected in HCN1 gene is a deletion of three amino acids.…”
Section: Discussionmentioning
confidence: 83%
“…The second patient [# 80], was carrier of a known mutation, p.Arg2726Trp, reported as associated with isolated skeletal features of MFS [Milewicz et al, 1995]; he showed skeletal and ocular involvement, absence of cardiovascular signs and of dural ectasia (DE) on lumbo-sacral MRI. He inherited the mutation from the mother who did not show the phenotype [Buoni et al, 2004].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Only two of our 81 patients were carriers of mutations in C terminus region. Both showed skeletal involvement [Buoni et al, 2004]; one also had aortic root dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a single nucleotide substitution in the same codon, causing a preterminal stop codon, was previously described in a Norwegian patient displaying a classic MF phenotype with ectopia lentis, thoracic aorta dilation and systemic features 72 . The other patient showed two mutations, one (Arg2726Trp) was previously associated with variable clinical phenotypes, including mitral valve prolapse (MVP) and myopia 69 , isolated skeletal features 73 , combined skeletal and ocular manifestations 74 , mild skeletal abnormalities 75 ; and a family in which the mutation displayed incomplete penetrance 76 . This mutation was reported in one chromosome of the 1000Genomes and NHLBI Exome Variant Server databases as rs61746008 (http://www.1000genomes.…”
Section: Marfan Syndrome Bav and Fbn1 Mutationsmentioning
confidence: 99%